The Role of Political Communication in School Curriculum: Its Impact on Student Activism - Jamil, Achmad; Sari, Afrina; Jati, Rocky Prasetyo; Umaimah, Umaimah; Vera, Nawiroh; Toni, Ahmad (Al-Qalam Institue, 2025)
This study aims to analyze the role of political communication integration in the school curriculum on its impact on student activism in junior high schools. The study is based on the increasing role of civic education in shaping students' political participation, especially in the digital era, where students' have easy access to political information through various social media platforms. This study uses a qualitative approach with a case study type. Data collection techniques include interviews, observations, and documentation taken from students, teachers, and activities at school and data analysis with the Miles and Huberman approach. The findings of this study that political communication in class and extracurricular activities increases students' knowledge of politics and their intention to participate in elections. Integration of political communication through discussion and use of social media enriches students political views and encourages them to voice political opinions openly. Civic learning experiences at school serve as strong predictors of students' offline political involvement, including in social movements and campaign activities. The implications of this study indicate the importance of political education in schools to form students who are more informed, critical, and active in political life, as well as strengthening the role of schools as agents of social change in building political awareness of the younger generation.